Impacts of cross ventilation applied to an emergency shelter in a container, through computer simulations with BIM-BES integration - Mata, Larissa Prado da; Dutra, Julia Toledo; Maciel , Ana Carolina Fernandes; Costa, Bruno Barzellay Ferreira da (Brazilian Journal of Production Engineering, 2025)
With the increase in the occurrence of disasters and, consequently, the growing demand for emergency housing, there is a need for a quick and viable construction solution. Containers are suitable in this context due to their modularity, which addresses these requirements. Despite the advantages, the use of containers for housing requires attention in terms of thermal performance, since they have a steel shell, which favors heating inside the module. Studies have shown that the use of thermal insulation in the composition of walls and ceilings helps to improve indoor thermal conditions, but it is not enough to provide adequate levels of performance. Therefore, this study proposes analyzing different cross-ventilation approaches as a solution to be combined with insulating materials to improve the thermal performance of this type of housing. For this purpose, computational fluid dynamics simulations were carried out for five modules with different window layouts. Two software packages were used for simulations, which allowed analysis of the distribution of ventilation and air temperature. The results indicate that the most efficient strategy was the configuration with conventional front openings combined with elevated openings on the opposite walls. In addition, the use of two software packages made the analysis comprehensive and reliable.
Keywords: Habitações emergenciais; Contêiner; Ventilação Cruzada; CFD